Isolation and Characterization of a Competition-Defective Bradyrhizobium japonicum Mutant - Bhagwat, Arvind A. (1991)
Tn5 mutagenesis was coupled with a competition assay to isolate mutants of Bradyrhizobium japonicum defective in competitive nodulation. A double selection procedure was used, screening first for altered extracellular polysaccharide production (nonmucoid colony morphology) and then for decreased competitive ability. One mutant, which was examined in detail, was deficient in acidic polysaccharide and lipopolysaccharide production. The wild-type DNA region corresponding to the Tn5 insertion was isolated, mapped, and cloned. A 3.6-kb region, not identified previously as functioning in symbiosis, contained the gene(s) necessary for complementation of the mutation. The mutant was motile, grew normally on minimal medium, and formed nodules on soybean plants which fixed almost as much nitrogen as the wild type during symbiosis.